Comparison and Analysis of Service Oriented Architecture - Kaur, Parneet (My University, 2017)
In today’s market, companies in the financial services have a common requirement to handle large amount of information with a high level of security and accuracy and provide on demand services. Innovative technology has been leveraged to endorse progressively complicated network of world-wide financial transactions which is managed by the financial services industry. Service Oriented Architecture (SOA) is becoming a popular access for integrating and designing enterprise applications. SOA enforce business services to deliver well defined services using a set of loosely couple services. Web services intended to be independent building blocks of Service Oriented Architecture. Web services are self contained. It provides a better alignment of IT with business vision, effective reuse of services, reduced cost of development and interoperability. SOA has its limitations and inherent issues. In this research, principles of SOA, benefits, limitations and challenges of SOA are discussed. We develop Currency exchange application based on Simple Object Access Protocol (SOAP) and Representational State Transfer (REST). It is important to select appropriate interaction styles i.e., either SOAP or REST for building SOA services. Choosing service interaction style is an important architectural decision for designers and developers, as it influences the underlying requirements for implementing SOA service solutions. In this study, the performance of currency exchange application based on SOAP and REST is compared. Since SOA services operate over network response time are considered as a metrics parameter for evaluation. Keywords: Service Oriented Architecture, Business Process Execution Language, Representational State Transfer, Simple Object Access Protocol, Web Service.
Master of Engineering -CSE
Keywords: Service Oriented Architecture; Business Process Execution Language; Representational State Transfer; Simple Object Access Protocol; Web Service